SANKSI HUKUM BAGI APARATUR SIPIL NEGARA TERLIBAT DALAM PARTAI POLITIK - Oktarina, Evi (Solusi, 2020)
Factors causing State Civil Apparatus (ASN) to participate in political parties are political intervention by State officials, ASN feel that their income or salary as ASN has not fulfilled the needs of life and the quality of its own human resources. While the legal sanctions for ASN involved in political parties namely to the ASN will be dismissed with no respect, this is as stated that ASN employees must be free from the influence and intervention of all groups and political parties (Article 9 (2)) of the ASN Law